Using Facebook as a Learning Management System: Experiences of Pre-service Teachers - Filiz KALELIOĞLU (Informatics in Education, 2017)
The purpose of this study was to examine students' experiences using Facebook as a learning management system during a course. The study participants were 18 junior education faculty students attending a compulsory distance education undergraduate course delivered by the Computer Education and Instructional Technology Department at a university in Turkey. Upon completion of the 14-week Facebook-based course, participants were requested to answer nine open-ended questions. The results of content analysis show some advantages and some problematic aspects to using Facebook as a learning management system (LMS). Most students were satisfied with their learning experience using Facebook. The students favoured some features and situations, while other students saw the same things as being problematic. They also appreciated the sharing of course materials, instant messaging, opportunity to upload files, having discussions and getting instant notifications. A few students had negative thoughts about sharing materials in terms of accessing pre-uploaded files. However, their thoughts about synchronous and asynchronous communication were all positive. In particular, all students favoured the instant Facebook communications with their instructor and engagement in discussions. Almost half of the students had positive thoughts about the usefulness of Facebook in education. When these positive thoughts were examined, the students were found to consider that Facebook could be used as a LMS because it has many similar features.